Distance learning in the work of the section of mathematics of the Small Academy of Sciences of Ukraine (Pedagogy of Higher and Secondary Education, 2021)
In the article the question of organization and functioning of the distance course for the listeners of section of mathematics of the Small academy of sciences is examined. The structure of cource and his purpose is described.
Keywords: out-of-school education; Small academy of sciences; distance education